Debt, guilt and form in (post-) Celtic Tiger Ireland. Issue 5 (4th May 2021) - Flannery, Eoin
ABSTRACT: The paper will look at two Irish literary texts from the mid-1990s up to the present day, and will read these texts in terms of their dramatisation of the politics of debt and guilt. Attention will be given to how different literary genres narrated debt and guilt in Irish society under the sway of the globalised Celtic Tiger economy. An analysis of Denis O'Driscoll's poem, 'The Celtic Tiger' will be presented first of all, as the poem is instructive on Ireland's new slew of performed identities during the economic 'boom', and the poem will be attended to in terms of the cultural politics of performance, desire and affect. Subsequently the paper will analyse Claire Kilroy's novel, The Devil I Know, an analysis that will be underpinned by a theoretical framework that focuses on how debt and guilt are formative of the modern sovereign subject. The arguments forwarded in the paper will take significant theoretical guidance from both Friedrich Nietzsche and Maurizio Lazzarato.